Evaluasi Kualitas Tanah Sawah Berbasis Sistem Informasi Geografis di Kecamatan Kediri untuk Menentukan Arahan Pengelolaan Tanah - Pramudita, I Gede Made; Kartini, Ni Luh; Trigunasih, Ni Made; Saifulloh, Moh (Fakultas Pertanian Universitas Udayana, 2024)
Geospatial Evaluation of Soil Quality in Rice Fields: A GIS-Based Approach for Informed Soil Management in Kediri District. Intensive land use, devoid of conservation efforts, results in a decline in soil quality and diminished crop yields. This research aims to assess the quality of rice fields, identify limiting factors, and offer guidance for appropriate soil management in accordance with the conditions of rice fields in Kediri District. The study was conducted from June 2023 to January 2024 in Subak’s rice fields in Kediri District, Tabanan Regency. The survey method was employed for soil sample collection based on the Land Unit map. Samples were purposively taken and composited, followed by testing for parameters based on the 10 Minimum Data Sets. Research data was presented in map form using QGIS 3.28.5 software. The results, obtained by calculating the Soil Quality Index (SQI), indicate that the quality of rice fields in Kediri District is classified as good (93.7%) in Land Units I, II, IV, and V, with respective SQI values of 24.00, 21.00, 24.33, and 24.00. Additionally, it is classified as very good (6,3%) in Land Unit III, with an SQI value of 19.33. Limiting factors identified include soil bulk density, soil texture, organic carbon content, cation exchange capacity, base saturation, total nitrogen, available phosphorus, and microbial biomass carbon. The recommended soil management practices include the application of organic fertilizer, urea, and TSP/SP-36.